Improved Privacy over Authentication of K-Nearest Neighbor Query on Spatial Network - P.Dhamodharan, V.Srilakshm, (International Journal of Scientific Research and Management (IJSRM), 2015)
Security is evolving to be an important aspect to be taken into our mind due to the eternally altering globe of worldwide data communications, inexpensive Internet connections, and fast-growing technology development. One of the fundamental requirement is security since many of world wide computing seems to be not secured. When the information gets travelled via Internet it has a wide variety of intermediate points and it gets easily hacked despite of many security techniques. Generally a user when surfers for an particular data the search panel is the area where the user enters his query for which the user needs to get the particular data While surfing the user information such as IP address of the user, area of user will be stored in the outsourced server. Since many of the outsourced servers does not provide high security user information such as area when gets hacked by some unauthenticated person then it will cause several sufferings to the authorized user. The main theme is to focus on the security of the user. Combination of Hilbert curve along with transformation and Voronoi Network provide better results when compared with existing techniques in this domain